1997
DOI: 10.1021/jp963022+
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of NH3 Formation by the Hydrogenation of Atomic Nitrogen on Rh(111)

Abstract: The reaction between atomic nitrogen and H 2 has been studied in order to elucidate the mechanism of NH 3 formation on Rh(111). Atomic nitrogen layers of 0.10 monolayer (ML) coverage were obtained by adsorbing NO at 120 K and selectively removing the atomic oxygen from dissociated NO by reaction with H 2 at 375 K. The rate of NH 3 formation is first order in the atomic nitrogen coverage and linearly proportional to the H 2 pressure below 5 × 10 -7 mbar. Static secondary ion mass spectrometry (SSIMS) indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…Assuming a value of 0.68 ML for the NO-saturated surface, calibration toward the NO uptake curve indicated that an atomic nitrogen coverage of 0.10 ML was obtained starting from an NO exposure of 0.25 langmuir. The procedure has been described in detail in a previous publication on the hydrogenation of atomic nitrogen …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Assuming a value of 0.68 ML for the NO-saturated surface, calibration toward the NO uptake curve indicated that an atomic nitrogen coverage of 0.10 ML was obtained starting from an NO exposure of 0.25 langmuir. The procedure has been described in detail in a previous publication on the hydrogenation of atomic nitrogen …”
Section: Resultssupporting
confidence: 88%
“…The procedure has been described in detail in a previous publication on the hydrogenation of atomic nitrogen. 18 Figure 1 shows the TPRS spectra of H 2 (2 amu), HCN (27 amu), N 2 (28 amu), and C 2 N 2 (52 amu) obtained from a Rh-(111) surface covered with 0.10 ML of N ads and various amounts of ethylene coadsorbed at 120 K. We also monitored CH 3 CN (51 amu) and NH 3 (17 amu), but these products were not detected. For comparison, we have added the N 2 desorption spectrum obtained from a surface solely covered with 0.10 ML of atomic nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of such species has been suggested in the first oscillatory work over a Rh field emitter, 25 as a possible cause of the observed high emission, because NH x is an electropositive species. 30 Under the conditions of a large excess of H 2 , formation of NH x intermediates is not impossible. 9 In photoemission electron microscopy ͑PEEM͒ work on Rh͑111͒, NH x was also suggested as a possible species for creating low work function areas as an alternative to the present sub-surface oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…The order of ammonia formation in the coverage of N atoms equals nϭ1, as follows from the straight line plot of ln N versus time, measured at 375 K and a constant pressure of 2ϫ10 Ϫ7 mbar of H 2 . 6 The order in hydrogen was determined at 375 K and H 2 pressures between 5ϫ10 Ϫ8 and 10 Ϫ6 mbar, for a fixed reaction time of 160 s, ͑see Fig. 3͒.…”
Section: Hydrogenation Of N Adsmentioning
confidence: 99%